Single-channel multiplexing without melting curve analysis in real-time PCR - Lee, Young-Jo (Sci Rep, 2014)
Multiplex real-time PCR with quantification of targets in a single fluorescence channel has been the demand in biotechnology industry. Here, we develop a novel analytical real-time PCR technique to detect multiple targets in a single fluorescence channel without melting curve analysis. In this technique, we show the intensity of the fluorescence signals of two discrete T(m) targets is different at certain temperatures called detection temperatures, by which a high T(m) target can be detected regardless of a low T(m) target. We then identify the low T(m) target by utilizing a change of the fluorescence signals between two different detection temperatures. Furthermore, it enables us to determine quantification of each target in a single channel, possibly facilitating convenient patient care for drug treatment in clinics.